The association between second trimester ultrasound fetal biometrics and gestational diabetes. (September 2022) - Andersen, Anna S.; Linneberg Rathcke, Sidsel; Tang Christensen, Trine; Sørensen, Anne
Highlights: Fetal biometrics >90th centile at 20 weeks is significantly associated with GDM. In GDM pregnancies fetal overgrowth may be present already at 20 weeks. Such finding underlines the importance of early GDM diagnosis and treatment. Abstract: Objective: Gestational diabetes mellitus (GDM) is the most common metabolic complication of pregnancy. The incidence of GDM is increasing worldwide and 5–25% of pregnancies are diagnosed with GDM depending on screening strategies and diagnostic criteria. GDM may lead to obstetric complications and increases the risk of adult metabolic disease in the offspring. Timely identification of GDM allows for regulation of maternal glucose levels which may reduce the obstetric complications considerably. The aim of this study is to investigate the association between second trimester ultrasound biometrics and GDM. Study Design: This is a retrospective cohort study including 2697 singleton pregnancies attending second trimester ultrasound scan at 20 + 0 to 20 + 6 weeks' gestation and giving birth at Aalborg University Hospital in the year 2020. Ultrasound measurements included head circumference (HC), abdominal circumference (AC), femur length (FL) and estimated fetal weight (EFW) by Hadlock's formula. Women with pregestational diabetes were excluded. GDM screening was performed on indication using oral-glucose-tolerance-test (OGTT) including 75 g glucose and a 2-hour serum glucose value ≥ 9 mmol/L was considered diagnostic. The association between fetal biometrics and GDM was investigated by logistic regression. Results: A total of 174 (6.5 %) were diagnosed with GDM. The incidence of GDM in pregnancies with biometrics above the 90th centile was; FL: 10.5 %, HC: 8.8 %, AC: 7.6 %, EFW: 9.3 %. Fetal biometrics above the 90th centile was significantly associated with GDM; ORFL  = 2.07, p = 0.001; ORHC  = 1.89, p = 0.001; ORAC  = 1.63, p = 0.033; OREFW  = 1.64, p = 0.036. This association remained significant for HC and FL when adjusted for maternal obesity (Body Mass Index ≥ 27): ORHC(adj)= 1.56, p = 0.019; ORFL(adj)  = 1.57, p = 0.049. Conclusion: At the second trimester scan, fetal biometrics above the 90th centile increase the risk of GDM. In pregnancies that are later diagnosed with GDM fetal growth is increased already at the second trimester scan. Such knowledge underlines the importance of early identification of GDM.